2017
DOI: 10.5114/ada.2017.67073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the serum zinc level in patients with vitiligo

Abstract: IntroductionVitiligo is an acquired, idiopathic disorder characterized by circumscribed depigmented macules and patches, which affects approximately 0.1–2% of the general population worldwide. Zinc is an essential trace element that is necessary for growth and development at all stages of life. Some studies have reported an association between serum zinc levels and vitiligo.AimTo measure the serum zinc level in patients with vitiligo compared to healthy subjects.Material and methodsOne hundred patients with vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 25 publications
3
20
0
5
Order By: Relevance
“…Rostami Moghaddam and colleagues (13) reported lower zinc levels in patients with vitiligo. Mirnezami and Rahimi (5) also reported low serum zinc levels in generalized patients with vitiligo.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rostami Moghaddam and colleagues (13) reported lower zinc levels in patients with vitiligo. Mirnezami and Rahimi (5) also reported low serum zinc levels in generalized patients with vitiligo.…”
Section: Discussionmentioning
confidence: 98%
“…It is plausible that the deficiency of both vitamin D and zinc levels due to their role in monogenesis, can affect disease progression and severity. However, different studies have reported conflicting results regarding the vitamin D and zinc levels in these patients (4)(5)(6)(13)(14)(15). Also, the association between vitiligo and thyroid disease is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, our results were consistent with a number of recent studies showing a significant decrease in zinc levels of vitiligo patients compared to healthy controls. [8][9][10] On the contrary some results refuted this relation and established no significant difference in serum zinc levels between vitiligo patients and healthy controls. 11 One study found zinc serum levels to be statistically higher in patients when compared to controls while another study found zinc serum levels insignificantly higher in patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Obtained serum samples were stored at -80 °C until use. For determination of Zn and Cu levels in serum, samples were diluted 10 times with ultrapure water without preliminary preparation and read against a standard chart using the method mentioned above, according to Mogaddam et al [5] and Michalska-Mosiej et al [6]. Each serum sample was measured at least 3 times.…”
Section: Methodsmentioning
confidence: 99%